Comparatism in the Neoplatonic Pantheon of Late Antiquity: Damascius, De Princ. III 159.6–167.25 - Mihai, Adrian (Numen, 2014)
In the following paper, we will look at the Neoplatonic pantheon as found in Damascius and at his comparatist method, which is centered on the principle of sumphōnia. This hermeneutical tool is used to reconcile or harmonize the doctrines of Plato sand Aristotle with other Greek and foreign theological traditions. We will see this at play in a passage from the last part of Damascius’ treatise on Problems and Solutions Concerning First Principles (III 159.6–167.25). In this section, Damascius, the last diadoch of the Platonic school of Athens, is trying to show that his ‘Platonic’ theology is in accordance not only with Greek wisdom (as represented by the Chaldean Oracles, Orphism, Homer, Hesiod and Pythagoreanism), but also with the oldest traditions of inspired religion, such as the Babylonian, Persian, Sidonian, Phoenician and Egyptian traditions. We will try to show that Damascius is establishing here a one-to-one correspondence between these Oriental and Hellenic theologies.